2020
DOI: 10.21203/rs.2.19709/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of quitting water pipe during pregnancy on Anthropometric measurements at birth: a population-based prospective cohort study in South of Iran

Abstract: Background: Evidence regarding health effects of tobacco cessation during pregnancy is mainly restricted to cigarette while water pipe is the preferred method of tobacco smoking among women in the Middle-East. The present ‎study aimed to assess the effects of cessation of water pipe during pregnancy on ‎birth anthropometric measures in the south of Iran.Methods: Data on 1,120 singleton pregnancies (response rate=93.4%) from a population-based prospective cohort study in suburban communities in Bandar Abbas cit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The results of the latest STEPS survey in Iran showed that water pipe is a prevailed mode of smoking in the south of Iran, where women used it more frequently than the rest of the country (7). Detrimental effects of water pipe smoking on pregnancy outcomes have been reported previously (2,5,8). LBW is also linked to the excess intake of caffeine; whereas its adverse effect on pregnancy outcome has not been fully worked out (9)(10)(11).…”
Section: Introductionmentioning
confidence: 98%
“…The results of the latest STEPS survey in Iran showed that water pipe is a prevailed mode of smoking in the south of Iran, where women used it more frequently than the rest of the country (7). Detrimental effects of water pipe smoking on pregnancy outcomes have been reported previously (2,5,8). LBW is also linked to the excess intake of caffeine; whereas its adverse effect on pregnancy outcome has not been fully worked out (9)(10)(11).…”
Section: Introductionmentioning
confidence: 98%